The characteristics of the ability to maintain static balance depending on the engagement of visual receptors among the elite sumo wrestlers - Rynkiewicz, T.; Zurek, P.; Rynkiewicz, M.; Starosta, W.; Nowak, M.; Kitowska, M.; Kos, H. (Archives of Budo, 2010)
Background and study aim: Since the ability to maintain balance is significant to efficient fighting, research was carried out in order to determine the level of the ability to maintain static balance among the Polish elite of sumo sportsmen depending on the engagement of visual receptors. Material and methods: Research group comprised 41 best Polish male and female sumo wrestlers. To evaluate the ability to maintain static balance the posturographical method was employed. The following measurements were made: with eyes open (EO), with eyes closed (EC) and in conditions of feedback (FB). Results: The closing of the eyes resulted in the increase of ACOP. The introduction of feedback had an effect on the obtainment of ACOP lowest values. The differences were not statistically significant. The change in the value of ACOP results from a modified number of deflections as well as their varied range. The changes in the number of deflections in the frontal and the midline plane were subject to analysis for they are considered to be the basic factors accounting for the reaction of the subjects to the change in the engagement of visual receptors. It was claimed that both the visual analyzers switch-off and the introduction of feedback had an effect on the increase in the number of deflections. The value of NDAP rose more significantly than the value of NDFP. Conclusions: The elimination of the engagement of visual receptors in the maintenance of static balance among the best Polish sumo sportsmen has a detrimental effect on the basic characteristics of COP. Increased is the value of ACOP and NDFP, especially that of NDAP. The introduction of FB during the measurement of the ability to maintain static balance enables the limitation of ACOP. Its lesser value is achieved due to an increase in the number of COP oscillations, particularly in the midline plane. The ability to take advantage of FB in the maintenance of static balance proves its high developmental level. In comparison with competitors of other sports as well as those not training, sumo sportsmen achieved lower values of ACOP in the majority of cases.